1887 Or. Code 977-78, tit. 2, ch. 8, § 1969 (Vol. 1) - (:unkn) unknown (My University, 1887)
Prohibited the concealed carry of any revolver, pistol, or other fire-arm any knife, dirk, dagger, slung-shot, metal knuckles, or any instrument which could inflict injury.Violators guilty of a misdemeanor, punished by fine not less than ten but no more than two hundred dollars, or imprisonment not less than five but no more one hundred days, or both.
Keywords: CARRY - CONCEALED